Dynamics and control of advanced structures and machines (Springer, 2017)
The papers in this volume present and discuss the frontiers in the mechanics of controlled machines and structures. They are based on papers presented at the International Workshop on Advanced Dynamics and Model Based Control of Structures and Machines held in Vienna in September 2015. The workshop continues a series of international workshops held in Linz (2008) and St. Petersburg (2010).
Keywords: Control theory -- Congresses.; Structural dynamics -- Congresses.; Mechanical engineering -- Congresses.; elektronické knihy; electronic books